Antioxidant responses ofin vitroshoots of Deschampsia antarcticato Polyethylene glycol treatment - Zamora, Pablo; Rasmussen, Susana; Pardo, Ariel; Prieto, Humberto; Zúñiga, Gustavo E. (Antarctic Science, 2010)
Abstract To understand the adaptability to environmental stresses by Deschampsia antarctica , one of the two vascular plants growing in Antarctica, we analysed the activity of several antioxidant enzymes, including peroxidase (POD, EC 1.11.1.7), ascorbate peroxidase (APX, EC 1.11.1.11), catalase (CAT, EC 1.11.1.6)) and glutathion reductase (GR, EC 1.6.4.2), in shoots subjected to drought stress (PEG-8000, -0.3 MPa). Additionally, levels of total phenolic compounds, flavonoids and ascorbate, were determined. The content of malondialdehyde (MDA), chlorophyll and hydrogen peroxide did not change as a result of PEG-8000 treatment. In addition, treated plants showed higher enzymatic activity of CAT, POD and GR in shoots than control plants. In addition, a high capacity to scavenge free radicals was also detected in stressed plants. These results seem to indicate that in D. antarctica tolerance of drought stress is associated with enhanced activity of antioxidant enzymes and free radical scavenging capacity.